2017
DOI: 10.1038/oncsis.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous loss of B lineage transcription factors leads to pre-B leukemia in Ebf1+/–Bcl-xLTg mice

Abstract: Early B-cell factor 1 (EBF1) plays a central role in B-cell lineage specification and commitment. Loss of this critical transcription factor is strongly associated with high-risk, relapsed and therapy-resistant B–cell-acute lymphoblastic leukemia, especially in children. However, Ebf1 haploinsufficient mice exhibit a normal lifespan. To determine whether prolonged survival of B cells would enable tumorigenesis in Ebf1 haploinsufficient animals, we generated Ebf1+/–Bcl-xLTg mice, which express the anti-apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Additionally, our experiments did not examine the potential to preserve RGC function, which should be a priority in a model system better suited to clinical examination. Translational application of BCLX L gene therapy will also require evaluating the safety issues associated with long-term expression of this anti-apoptotic protein, including its possible effects on tumorigenesis [ 53 , 54 ] and increased susceptibility to viral infections [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our experiments did not examine the potential to preserve RGC function, which should be a priority in a model system better suited to clinical examination. Translational application of BCLX L gene therapy will also require evaluating the safety issues associated with long-term expression of this anti-apoptotic protein, including its possible effects on tumorigenesis [ 53 , 54 ] and increased susceptibility to viral infections [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another study also analyzed molecular differences between B-ALL and T-ALL and found VPREB3 as a methylation and expression signature gene [101]. EBF1 is a transcription factor involved in B-cell lineage specification and commitment [102], which explains its increased expression in B-ALL compared to T-ALL ( Table 3 ). Deletions of EBF1 have been found to be associated with B-ALL [102,103].…”
Section: Resultsmentioning
confidence: 99%
“…EBF1 is a transcription factor involved in B-cell lineage specification and commitment [102], which explains its increased expression in B-ALL compared to T-ALL ( Table 3 ). Deletions of EBF1 have been found to be associated with B-ALL [102,103]. NDST3 encodes an enzyme that plays a role in heparan sulfate metabolism [104].…”
Section: Resultsmentioning
confidence: 99%
“…In this case, gene therapy using AAV would require careful evaluation of the safety issues related to the expression of an anti-apoptotic protein in the long term. Among these safety issues, special attention should be given to increased susceptibility to viral infections and possible effects on tumorigenesis [ 39 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%